Pengembangan Media Animasi Pembelajaran Interaktif Pokok Bahasan Gaya Pada Matapelajaran IPA Kelas IV SD - Muzakki; Mohammad Efendi; Abdul Manan (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2016)
In order for the abstract concepts taught in elementary science subjects to be accepted by students, a medium or intermediary is needed to concretize the material. This media development uses the Sadiman (2008) model, with material on the subject of style. The validity of the development results is indicated by the fulfillment of the criteria obtained from the test results, namely media experts with a validity level of 90.56%, material experts at 91.11% and individual students at 95.56%, small group students of 94.44% and large group students of 91.17%. Based on the results of this validation, it was concluded that the interactive learning animation media on the science subject subject of style was valid or feasible.